Charakterisierung und Modellierung des Bruchverhaltens von Punktschweißverbindungen in pressgehärteten Stählen - Hein, David; Meschut, Gerson; Hahn, Ortwin; Klokkers, Frederik (11. LS-DYNA Forum 2012)

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, Reuven; Nudelman, Ilia; Polevoy, Gleb (Infocom'2012, Orlando, Florida)

Talking like a book. Investigating colloquialization as a change in written English - Mindt, Ilka (Oralité(s) et écriture(s))

Change in Contemporary English. A Grammatical Study - Mindt, Ilka; Leech, Geoffrey; Hundt, Marianne; Mair, Christian; Smith, Nicholas (Archiv für das Studium der neueren Sprachen und Literaturen 164: 249: 2)

Design of an exact data deduplication cluster - Kaiser, Jürgen; Meister, Dirk; Brinkmann, André; Effert, Sascha (Proc. Symp. on Mass Storage Systems and Technologies (MSST))

Editorial for Algorithmic Aspects of Wireless Sensor Networks - Dolev, Shlomi; Scheideler, Christian (Theor. Comput. Sci.)

Selfish Distributed Optimization - Monien, Burkhard; Scheideler, Christian (Euro-Par 2012 Parallel Processing - 18th International Conference, Euro-Par 2012, Rhodes Island, Greece, August 27-31, 2012. Proceedings)

Materielles und Immaterielles Kulturerbe - global, regional, glokal? - Seng, Eva- Maria (Vortrag auf der Tagung "Kulturerbe Baden-Württemberg" des Museumsverbandes Baden-Württemberg e.V., Stuttgart 09.-10.03.2012)

Eine gewinnbringende Kooperation zwischen Museum und Universität - Seng, Eva- Maria (Freilichtmagazin 2012. Mitteilungen aus dem LWL-Freilichtmuseum Detmold – Westfälisches Landesmuseum für Volkskunde H7)

Revisionen: Städtebau im 18. Jahrhundert - Seng, Eva- Maria; Gieser, Laura; Göttmann, Frank (Francia. Forschungen zur westeuropäischen Geschichte, Bd. 39)

Das Ende des Nachkriegsstädtebaus: Stadtumbau Ost - Stadtumbau West: neue Mitte Ulm und Potsdamer Mitte - Seng, Eva- Maria (Kunst und Architektur in Mitteldeutschland. Thomas Topfstedt zum 65. Geburtstag)

Utopie und Architektur - Seng, Eva- Maria; Saage, Richard (L’Architecture engagée. Manifeste zur Veränderung der Gesellschaft (Publikation zur Ausstellung des Architekturmuseums der TU München in der Pinakothek der Moderne 14. Juni bis 02. September 2012)

Deutschsprachige Literatur(en) seit 1989

Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben

Schemata und Praktiken

Deutschsprachige Literatur(en) seit 1989. Zur Einführung - Eke, Norbert Otto; Elit, Stefan (Zeitschrift für deutsche Philologie (Sonderheft "Deutschsprachige Literatur(en) seit 1989" zum Band 131))
Angaben zur Herausgeberschaft: Hg. von Norbert Otto Eke und Stefan Elit

Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben. Dreißig Jahre Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller - Eke, Norbert Otto (Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben)

Werner Fritsch: „Theater gegen alles Theater“ - Eke, Norbert Otto (Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben)

Lea Singer: Nähe in der Distanz – Humilitas und Emphase - Eke, Norbert Otto (Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben)

Beobachtungen beobachten. Beiläufiges aus germanistischer Sicht zum Umgang mit einer Literatur der Gegenwärtigkeit - Eke, Norbert Otto (Doing Contemporary Literature. Praktiken, Wertungen, Automatismen)

“Komm Leonce, halte mir einen Monolog, ich will zuhören”. Büchners eingestandener Stillstand - Eke, Norbert Otto (Commitment and Compassion. Essays on Georg Büchner. Festschrift for Gerhard P. Knapp)

Schreckliche Witze – Geschmacklose Wahrheiten oder “Jeder wirkliche Humor ist schwarz”. George Tabori und der ‘schwarze Humor’ - Eke, Norbert Otto (Politik und Ethik der Komik)

Der Verlust der Gattungsmerkmale. Drama nach 1945 - Eke, Norbert Otto (Handbuch Drama. Theorie, Analyse, Geschichte)

“Ich hab mich schon in der Erd”. Robert Schindels Gegen-Sprechen - Eke, Norbert Otto (Fährmann sein. Robert Schindels Poetik des Übersetzens)

Büchner und die Zeit - Eke, Norbert Otto (Georg Büchner und das 19. Jahrhundert)

Schemata und Praktiken: Einleitung - Eke, Norbert Otto; Conradi, Tobias; Ecker, Gisela; Muhle, Florian (Schemata und Praktiken)

Predicting production influences on adhesively bonded joints subjected to cyclic load - Teutenberg, Dominik; Hahn, Ortwin (Welding in the World)

Entwicklung einer Vorgehensweise zur Abschätzung der Einflüsse konstruktions- und fertigungsbedingter Toleranzen auf die mechanischen Eigenschaften von Klebverbindungen unter zyklischer Belastung - Teutenberg, Dominik

Analytische Abschätzung des Einflusses von Fertigungstoleranzen auf Klebverbindungseigenschaften unter zyklischer Belastung - Teutenberg, Dominik; Hahn, Ortwin; Meschut, Gerson (2. Doktorandenseminar Klebtechnik)

Scham als Verhaltenssteuerung im Recht – Rechtstheoretische Aspekte eines Phänomens - Krimphove, Dieter (Rechtstheorie)

Die Rolle des Gehirns nach Kreuzbandverletzungen - Ansatz für innovative Präventions- und Rehabilitationsprogramme - Baumeister, Jochen (ForschungsForum)

What the brain can tell us in musculoskeletal rehabilitation - Baumeister, Jochen (J Sport Medic Doping Stud)

Effects of induced fatigue on brain activity during sensorimotor control - Baumeister, Jochen; Reinecke, K; Schubert, M; Schade, J; Weiss, M (Eur J Appl Physiol)

The response of cortical alpha activity to pain and neuromuscular changes caused by exercise induced muscle damage - Plattner, K; Tam, N; Lambert, MI; Baumeister, Jochen

Approaching effective connectivity measures in exercise neuroscience - Schubert, M; Hansmeier, T; Koutsandreou, F; Reinecke, K; Weiß, M; Baumeister, Jochen

Divergente kortikale Aktivierung nach erschöpfendem Kraft und Ausdauertraining: eine EEG Studie - Reinecke, K; Schubert, M; Weiß, M; Baumeister, Jochen

Jonglieren steigert die Gehirnaktivität von Grundschülern - Koutsandreou, F; Cordes, M; Schubert, M; Weiß, M; Baumeister, Jochen

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Sievers, Sönke; Mokwa, Christopher Frederik
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Sievers, Sönke; Mokwa, Christopher Frederik
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Application and Evaluation in the Automotive Domain - Fockel, Markus; Heidl, Peter; Höfflinger, Jens; Hönninger, Harald; Holtmann, Jörg; Horn, Wilfried; Meyer, Jan; Meyer, Matthias; Schäuffele, Jörg (Model-Based Engineering of Embedded Systems)
This chapter summarizes the application and evaluation of the SPES engineering methodology in the automotive domain. After introducing the particular domain characteristics, we state some research questions that we have investigated. Some of the activities that address these research questions are presented in detail. We conclude that the SPES engineering methodology is a good basis for the development of automotive systems, but could be further refined to fit the particular needs of the domain.

Jamming-resistente MAC-Protokolle - Meith, Frank Ingo

Mobile WDM Backhaul Access Networks with Physical Inter-Base-Station Links for Coordinated Multipoint Transmission/Reception Systems - Biermann, T.; Scalia, L. (2011 IEEE Global Telecommunications Conference - GLOBECOM 2011)

Coordinated multipoint multiuser-MIMO transmissions over backhaul-constrained mobile access networks - Choi, Changsoon; Scalia, Luca; Biermann, Thorsten; Mizuta, Shinj (2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications)

Digital native oder digital naiv? Medienpädagogik der Generationen

Vermittlungswissenschaft in der Wissensgesellschaft - Meister, Dorothee M. (Erwägen Wissen Ethik. Jg. 23/2012 (Heft 3).)

Bildungschancen eröffnen durch inklusive Medienbildung - das Paderborner Recycling Projekt (pb.re.pc) - Kamin, A.-M.; Meister, Dorothee M. (Ludwigsburger Beiträge zur Medienpädagogik. Schwerpunkt "Inklusive Medienbildung" Ausgabe 15 / 2012)

Computer Games in the Context of Adolecents Media Behavior - Meister, Dorothee M.; Müller-Lietzkow, J.; Burkatzki, E.; Kröger, S. (Computer Games and New Media Cultures. A Handbook of Digital Games Studies)

Genesen und Spezifika jugendlichen Medienhandels - Meister, Dorothee M.; Meise, B. (Schriftenreihe Psychologie und Gesellschaft. Medien in unserer Gesellschaft - Chancen und Risiken)

Digitale Lernangebote bei älteren Berufstätigen: Zwischen Akzeptanz und Vorbehalt - Kamin, A.-M.; Ganguin, S.; Meister, Dorothee M. (Digital native oder digital naiv? Medienpädagogik der Generationen)

Medienpädagogik der Generation - Einführende Überlegungen - Ganguin, S.; Meister, Dorothee M. (Digital native oder digital naiv? Medienpädagogik der Generationen)

Hybrid functionals and GW approximation in the FLAPW method - Friedrich, Christoph; Betzinger, Markus; Schlipf, Martin; Blügel, Stefan; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
We present recent advances in numerical implementations of hybrid functionals and the GW approximation within the full-potential linearized augmented-plane-wave (FLAPW) method. The former is an approximation for the exchange–correlation contribution to the total energy functional in density-functional theory, and the latter is an approximation for the electronic self-energy in the framework of many-body perturbation theory. All implementations employ the mixed product basis, which has evolved into a versatile basis for the products of wave functions, describing the incoming and outgoing states of an electron that is scattered by interacting with another electron. It can thus be used for representing the nonlocal potential in hybrid functionals as well as the screened interaction and related quantities in GW calculations. In particular, the six-dimensional space integrals of the Hamiltonian exchange matrix elements (and exchange self-energy) decompose into sums over vector–matrix–vector products, which can be evaluated easily. The correlation part of the GW self-energy, which contains a time or frequency dependence, is calculated on the imaginary frequency axis with a subsequent analytic continuation to the real axis or, alternatively, by a direct frequency convolution of the Green function G and the dynamically screened Coulomb interaction W along a contour integration path that avoids the poles of the Green function. Hybrid-functional and GW calculations are notoriously computationally expensive. We present a number of tricks that reduce the computational cost considerably, including the use of spatial and time-reversal symmetries, modifications of the mixed product basis with the aim to optimize it for the correlation self-energy and another modification that makes the Coulomb matrix sparse, analytic expansions of the interaction potentials around the point of divergence at k=0, and a nested density and density-matrix convergence scheme for hybrid-functional calculations. We show CPU timings for prototype semiconductors and illustrative results for GdN and ZnO.

Controlling the Quality of Laser Sintered Parts Along the Process Chain - Rüsenberg, Stefan; Weiffen, R.; Knoop, F.; Schmid, Hans-Joachim (23rd Annual International Solid Freeform Fabrication Symposium)
The quality of laser sintered parts, in this work, manufactured by polymer laser sintering by using an EOSINT P395 Laser Sintering system, depends on several steps along the process chain. The first step is the characterization of the powder quality, whereas the rheological and physical investigations of nylon 12 powder are shown. By changing some important influencing factors, for example the powder ratio, the powder ageing and the moisture content, the influence on mechanical and physical properties, density and porosity, are investigated. The composition of the used powder is known. The previous process (storage conditions, etc.) as well as the laser sintering process (regarding energy density, temperature, etc.) is kept constant for the duration of this work. Regarding the post process in this work the cooling down phase is investigated as well. With an automatically blasting system it is possible to keep the post process parameters blasting distance and blasting time, constant. All of the tests will be performed using dry and conditioned test specimens. This work is showing the dependence on mechanical, rheological and physical parameters by varying important influencing factors along the laser sintering process quality chain.

Mechanical Properties as a Result of multitude of Parameters - Rüsenberg, Stefan; Schmid, Hans-Joachim (The European Forum on Additive Manufacturing)
Material properties of parts from additive manufacturing are influenced by a huge number of material, operational and job parameters. This work aims to identify the most important ones and to investigate mechanical properties as depending on those parameters. Test specimens were produced with standard PA12 powder on an EOSINT P390 and P395, respectively. The influence of the orientation and placement of parts in the building chamber were investigated systematically. The mechanical properties

Elementbasierte Erarbeitung von Konstruktionsregeln für additive Fertigung - Adam, Guido; Zimmer, Detmar

Untersuchung von Bauteilschäden elektrischer Antriebsstränge im Belastungsprüfstand mittels Statorstromanalyse - Zimmer, Detmar; Lessmeier, Christian; Hameyer, Kay; Piantsop Mbo'o, Christelle; Coenen, Isabel (ant Journal - Anwendungsnahe Forschung für Antriebstechnik im Maschinenbau)

Anforderungen an Bremssysteme in der industriellen Antriebstechnik - Kriegel, Nils-Peter; Wecker, Markus; Zimmer, Detmar (VDI-Konferenz Innovative Bremstechnik)

Untersuchung von Bauteilschäden elektrischer Antriebsstränge im Belastungsprüfstand mittels Statorstromanalyse - Lessmeier, Christian; Piantsop Mbo'o, Christelle; Coenen, Isabel; Zimmer, Detmar; Hameyer, Kay

Anforderungen an Bremssysteme der industriellen Antriebstechnik - Kriegel, Nils-Peter; Zimmer, Detmar (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Low friction Rotary Shaft Seal. Verlustleistungsreduziertes Dichtsystem - Nolte, Karsten; Zimmer, Detmar (International Sealing Conference)

Hierarchical optimization of coupled self-optimizing systems - Hölscher, Christian; Zimmer, Detmar; Keßler, Jan Henning; Kruger, Martin; Trächtler, Ansgar (IEEE International Conference on Industrial Informatics)

Entwicklung eines modularen Antriebssystems für Kautschukinnenmischer - Fiekens, Nicolas; Zimmer, Detmar; Michaelis, Stefanie; Schöppner, Volker; Hallmann, Tobias (DKT 2012. Deutsche Kautschuk Tagung)

Elektromechanische Antriebe - Zimmer, Detmar

Network Disruption and the Common Enemy Effect - Hoyer, Britta; De Jaegher, Kris
The phenomenon that groups or people work together when they face an opponent, although they have little in common otherwise, has been termed the "common enemy effect". We study a model of network formation, where players can use links to build a network, knowing that they are facing a common enemy who can disrupt the links within the network, and whose goal it is to minimize the sum of the benefits of the network. We find that introducing a common enemy can lead to the formation of stable and efficient networks as well as fragmented networks and the empty network.

Model-driven Performance Engineering of Self-adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen ({Proceedings of the 8th International ACM SIGSOFT Conference on Quality of Software Architectures (QoSA)})
Keywords: model-driven performance engineering; self-*; Self-adaptation; software performance

A Tax Paradox for Investment Decisions under Uncertainty - Gries, Thomas; Prior, Ulrich; Sureth-Sloane, Caren (Journal of Public Economic Theory)

Reactive absorption in chemical process industry: A review on current activities - Yildirim, Ömer; Kiss, Anton A.; Hüser, Nicole; Leßmann, Katharina; Kenig, Eugeny (Chemical Engineering Journal)

Strategy Planning of Collaborative Humanoid Soccer Robots based on Principle Solution - Low, Cheng; Aldemir, Mustafa; Aziz, Norheliena; Dumitrescu, Roman; Anacker, Harald (Proceedings of the 1st German-Malaysian Workshop, Hannover, 27. - 29. Jun. 2012)

Simulative Absicherung mechatronischer Systeme in der frühen Phase der Produktentstehung - Bauer, Frank; Gausemeier, Jürgen; Köchling, Daniel; Oestersötebier, Felix (Tag des Systems Engineerings)

Unterstützung des mechatronischen Entwurfs durch die effektive Suche nach Lösungselementen mithilfe von semantischen Technologien - Oestersötebier, Felix; Dziwok, Stefan; Bauer, Frank; Trächtler, Ansgar; Schäfer, Wilhelm; Gausemeier, Jürgen (Tag des Systems Engineerings)

Einheitliche Testumgebung für MiL und RCP mittels NI VeriStand am Beispiel eines Waschautomaten - Kruse, Daniel; Fast, Viktor; Schweers, Christoph; Trächtler, Ansgar (Virtuelle Instrumente in der Praxis (VIP 2012))

A Modelica Library for Real-Time Coordination Modeling - Pohlmann, Uwe; Dziwok, Stefan; Suck, Julian; Wolf, Boris; Loh, Chia Choon; Tichy, Matthias (Proceedings of the 9th International Modelica Conference 2012)

Safety Assurance for a Fault Tolerant Control System of an X-By-Wire Vehicle - Lurye, Oleg; Trächtler, Ansgar (Advanced Vehicle Control (AVEC))

Werkstoffeigenschaften handlaminierter Faserverbundkunststoffe, erfasst in realen und virtuellen Laboren der Mechanik unter Einsatz von Methoden zur Wissensorganisation - Koke, Isabel

Hierarchical Optimization of Coupled Self-optimizing Systems - Hölscher, Christian; Kessler, Jan Henning; Krüger, Martin; Trächtler, Ansgar; Zimmer, Detmar (10th IEEE International Conference on Industrial Informatics)

Hierarchical Hybrid Planning for a Self-Optimizing Active Suspension System - Esau, Natascha; Krüger, Martin; Rasche, Christoph; Beringer, Steffen; Kleinjohann, Lisa; Kleinjohann, Bernd (7th IEEE Conference in Industrial Electronics and Applications)

Model-Based Design of Mechatronic Systems by Means of Semantic Web Ontologies and Reusable Solution Elements - Oestersötebier, Felix; Just, Viktor; Trächtler, Ansgar; Bauer, Frank; Dziwok, Stefan (Proceedings of the ASME 2012 11th Biennial Conference on Engineering Systems Design and Analysis)

Methodology For Selecting The Modeling Depth Of Object-Oriented Behavioral Models - Lochbichler, Matthias; Schmuedderich, Tanja; Brökelmann, Jan; Trächtler, Ansgar (World Academy of Science, Engineering and Technology)

Robust Pareto Points with Respect to Crosswind of an Active Suspension System - Krüger, Martin; Witting, Katrin; Dellnitz, Michael; Trächtler, Ansgar (1st Joint International Symposium on System-Integrated Intelligence)

Approximation of Pareto-Optimal Systems using Parametric Model-Order Reduction - Krüger, Martin; Trächtler, Ansgar (7th Vienna International Conference on Mathematical Modelling)

Fahrerassistenzsystem für energie- und zeitoptimales Fahren durch prädiktive Geschwindigkeitsprofil-Planung

Automated Design of Reconfiguration Strategies Increases Reliability - Lurye, Oleg; Kromov, Ivan; Trächtler, Ansgar (Proceedings of Reliability, Avaliability and Maintainability Symposium)

Fahrerassistenzsystem für energie- und zeitoptimales Fahren durch prädiktive Geschwindigkeitsprofil-Planung - Gausemeier, Sandra; Trächtler, Ansgar; Jäker, Karl-Peter (13. Braunschweiger Symposium AAET)

Using Algorithmic Differentiation for the Multiobjective Optimization of a Test Vehicle - Ringkamp, Maik; Walther, Andrea; Reinold, Peter; Witting, Katrin; Dellnitz, Michael; Trächtler, Ansgar (EVOLVE)

Erhöhung der Verlässlichkeit eines innovativen Versuchsfahrzeugs mit Einzelradaktorik durch Rekonfiguration der Regelung - Lurye, Oleg; Trächtler, Ansgar (13. Braunschweiger Symposium AAET)

Cooperative transportation of a load using nonholonomic mobile robots - Loh, Chia Choon; Trächtler, Ansgar (Procedia Engineering)

Modellbasierter Entwurf zweier kooperierender Delta-Roboter - Teichrieb, Heinrich; Just, Viktor; Dziwok, Stefan; Pohlmann, Uwe; Schierbaum, Thomas; Trächtler, Ansgar (Berichtsband des Tag des Systems Engineering 2012)

Constrained Linear Quadratic Optimal Controller for Motion Control of ATMOS Driving Simulator - Al Qaisi, Imad; Trächtler, Ansgar (Driving Simulation Conference 2012 Europe - DSC 2012,)

Multi-robot Approach for Automation of an Industrial Profile Lamination Process - Bielawny, Dirk; Bruns, Torsten; Loh, Chia Choon; Trächtler, Ansgar (2012 International Symposium on Robotics and Intelligent Sensors (IRIS))

A self-correcting Approach for the Bending of Metal Parts - Damerow, Ulf-Hendrik; Borsig, Michael; Homberg, Werner; Trächtler, Ansgar (Key Engineering Materials Vols. 504-506 (2012))

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Model-based Design of Self-Correcting Strategy for a Punch Bending Machine - Borsig, Michael; Trächtler, Ansgar; Damerow, Ulf-Hendrik; Homberg, Werner (14th IFAC Symposium on Information Control Problems in Manufacturing, INCOM 2012,)

Human in the Loop: Optimal Control of Driving Simulators and New Motion Quality Criterion - Al Qaisi, Imad; Trächtler, Ansgar (IEEE International Conference on Systems, Man and Cybernetics - IEEE SMC 2012)

Analyzing Product Lifecycle Costs for a Better Understanding of Cost Drivers in Additve Manufacturing - Lindemann, C.; Jahnke, U.; Moi, M.; Koch, R. (23rd Annual International Solid Freeform Fabrication Symposium)
The costs of additive manufactured parts often seem too high in comparison to those of traditionally manufactured parts, as the information about major cost drivers, especially for additive manufactured metal parts, is weak. Therefore, a lifecycle analysis of additive manufactured parts is needed to understand and rate the cost drivers that act as the largest contributors to unit costs, and to provide a focus for future cost reduction activities for the Additive Manufacturing (AM) technology. A better understanding of the cost structure will help to compare the AM costs with the opportunity costs of the classical manufacturing technologies and will make it easier to justify the use of AM manufactured parts. This paper will present work in progress and methodology based on a sample investigated with business process analysis / simulation and activity based costing. In addition, cost drivers associated with metal AM process will be rated.

The MoSGrid Community From National to International Scale - Gesing, Sandra; Herres-Pawlis, Sonja; Birkenheuer, Georg; Brinkmann, André; Grunzke, Richard; Kacsuk, Peter; Kohlbacher, Oliver; Kozlovszky, Miklos; Krüger, Jens; Müller-Pfefferkorn, Ralph; Schäfer, Patrick; Steinke, Thomas (Proc. EGI Community Forum)

STIR: Software for Tomographic Image Reconstruction Release 2 - Thielemans, Kris; Tsoumpas, Charalampos; Mustafovic, Sanida; Beisel, Tobias; Aguiar, Pablo; Dikaios, Nikolaos; W Jacobson, Matthew (Physics in Medicine and Biology)

Parallel algorithm for computation of second-order sequential best rotations - Redif, Soydan; Kasap, Server (Int. Journal of Electronics)

Parallel Processor Design and Implementation for Molecular Dynamics Simulations on a FPGA Parallel Computer - Kasap, Server; Benkrid, Khaled (Journal of Computers)

Evaluierung medizinischer Volumenrendering-Algorithmen durch empirische Studien - Domik, Gitta; Arens, Stephan; Tünnermann, Jan; Scharlau, Ingrid Rose (FIfF-Kommunikation)
Keywords: Informatik; Visualisierung; Psychologie; Experimentaldesign

Introducing Google Chart Tools and Google Maps API in Data Visualization Courses - Zhu, Y. (IEEE Computer Graphics and Applications)

Teaching 3D Computer Animation to Illustrators: The Instructor as Translator and Technical Director - Koning, W. F. (IEEE Computer Graphics and Applications)